Measuring Microenterprise Profits : Don't Ask How the Sausage is Made - de Mel, Suresh (World Bank, Washington, DC, 2012)
A large share of the world's poor is self-employed. Accurate measurement of profits from microenterprises is therefore critical for studying poverty and inequality, measuring the returns to education, and evaluating the success of microfinance programs. But a myriad of problems plague the measurement of profits. The authors report on a variety of different experiments conducted to better understand the importance of some of these problems and to draw recommendations for collecting profit data. In particular, they (1) examine how far we can reconcile self-reported profits and reports of revenue minus expenses through more detailed questions; (2) examine recall errors in sales and report on the results of experiments which randomly allocated account books to firms; and (3) ask firms how much firms like theirs underreport sales in surveys like this, and have research assistants observe the firms at random times 15-16 times during a month to provide measures for comparison. The authors conclude that firms underreport revenues by about 30 percent, that account diaries have significant effects on both revenues and expenses but not on profits, and that simply asking profits provides a more accurate measure of firm profits than detailed questions on revenues and expenses.